Loop Diuretic Adjustments in Patients with Chronic Heart Failure: Insights from HF-ACTION - Fudim, Marat (Am Heart J, 2018)
BACKGROUND: The relationship between diuretic use or change in diuretic use and outcomes in chronic heart failure (HF) remains poorly defined. We evaluated the association between diuretic use and changes in health status, exercise capacity, and clinical events in a large randomized trial of subjects with HF. METHODS: HF-ACTION randomized 2331 outpatients with HF and ejection fraction ≤ 35% to aerobic exercise training versus usual care. We grouped patients according to loop diuretic use from baseline through 6 months: continued-use, never-use, initiated, discontinued. The association between diuretic use and changes in health status, exercise capacity, and clinical outcomes (all-cause mortality/hospitalization, CV mortality and HF hospitalization) through 12 months were assessed using Cox proportional hazards models and generalized linear regression models, respectively. RESULTS: A total of 2004 (86%) patients had complete data on diuretic use. There was no association between diuretic status and Kansas City Cardiomyopathy Questionnaire (KCCQ), 6-minute walk distance or peak VO2 in adjusted analyses (all P>0.05). A dose increase was associated with decrease in 6-minute walk distance (−4.25m, SE 1.12m, P<0.001) and change in KCCQ overall score (−0.56m, SE 0.24m, P=0.02). There were no between-group differences for all cause death or hospitalization comparing continuous use versus never-use (adjusted HR 0.91; 95%CI 0.72–1.15; P= 0.432). CONCLUSIONS: The initiation or discontinuation of diuretics over a 6-month time frame was not associated with a difference in mortality, hospitalizations, exercise or health status outcomes but a dose increase in HF patients was associated with worse exercise and health status outcomes.